Comparative Use of Production Factors for Self-Owned Farmers and Plasma in Palm Oil Farming and Their Relationship with Income in Air Kumba District, Banyuasin Regency - Khomeinie, Muhammad Ali; Thony Ak, Agoes; Kuwatno, Kuwatno (Journal of Science and Science Education, 2024)
The objectives of this research are 1) To determine the differences in the use of production factors by plasma and independent farmers in oil palm farming in Air Kumbang District, Banyuasin Regency, 2) To calculate the difference in income received by plasma and independent farmers in oil palm farming in Air Kumbang District Banyuasin Regency. The method used is a survey method of independent and plasma farmers in oil palm farming in Air Kumbang District, Banyuasin Regency. The data collected includes data sources from both primary and secondary data. To analyze the difference in income between plasma farmers' oil palm farming income and independent smallholders' oil palm farming income, the two middle value test is used. Based on the research results, it can be concluded 1) There are differences in the use of production factors for plasma farmers and independent farmers in the Air Kumbang District. The differences in the use of production factors result in differences in the level of production and productivity of oil palm farming, this is due to differences in palm oil farming business patterns, 2) There are differences in the income of plasma farmers and independent farming in Air Kumbang District.  Differences in the use of production factors are the main cause of both the use of fertilizers, herbicides and pesticides as well as the use of labor. This shows that farming management and the use of production factors can increase production and of course ultimately increase the income of oil palm farmers.